Development and preliminary validation of a virtual reality memory test for assessing visuospatial memory - Ko Woon Kim; Ko Woon Kim; Jong Doo Choi; Juhee Chin; Byung Hwa Lee; Jee Hyun Choi; Duk L. Na; Duk L. Na; Duk L. Na (Frontiers in Aging Neuroscience, 2023)
BackgroundVisuospatial memory impairment is a common symptom of Alzheimer’s disease; however, conventional visuospatial memory tests are insufficient to fully reflect visuospatial memory impairment in daily life.MethodsTo address patients’ difficulties in locating and recalling misplaced objects, we introduced a novel visuospatial memory test, the Hidden Objects Test (HOT), conducted in a virtual environment. We categorized HOT scores into prospective memory, item free-recall, place free-recall, item recognition, and place-item matching scores. To validate the VR memory test, we compared HOT scores among individuals with Alzheimer’s disease (AD), amnestic mild cognitive impairment (aMCI), and normal controls (NC), and also compared these scores with those of conventional neuropsychological tests. We tracked the participants’ movement paths in the virtual environment and assessed basic features, such as total distance, duration, and speed. Additionally, we performed walking trajectory pattern mining such as outlier and stay-point detection.ResultsWe designed and implemented the HOT to simulate a house’s living room and assess participants’ ability to locate hidden objects. Our preliminary results showed that the total HOT score differed among 17 patients with AD, 14 with aMCI, and 15 NC (p < 0.001). The total HOT score correlated positively with conventional memory test scores (p < 0.001). Walking trajectories showed that patients with AD and aMCI wandered rather than going straight to the hidden objects. In terms of basic features, the total duration was significantly greater in AD than in NC (p = 0.008). In terms of trajectory pattern mining, the number of outliers, which were over 95% of the estimated trajectory, was significantly higher in AD than in NC (p = 0.002). The number of stay points, an index in which participants stayed in the same position for more than 2 s, was significantly higher in patients with AD and aMCI compared with NC (AD vs. NC: p = 0.003, aMCI vs. NC: p = 0.019).ConclusionThe HOT simulating real life showed potential as an ecologically valid test for assessing visuospatial memory function in daily life. Walking trajectory analysis suggested that patients with AD and aMCI wandered rather than going straight toward the hidden objects.